Concerning colour: The effect of environment on type Ia supernova colour in the dark energy survey. Issue 2 (19th December 2022) - Kelsey, L; Sullivan, M; Wiseman, P; Armstrong, P; Chen, R; Brout, D; Davis, T M; Dixon, M; Frohmaier, C; Galbany, L; Graur, O; Kessler, R; et al.
ABSTRACT: Recent analyses have found intriguing correlations between the colour ( c ) of type Ia supernovae (SNe Ia) and the size of their 'mass-step', the relationship between SN Ia host galaxy stellar mass ( M stellar ) and SN Ia Hubble residual, and suggest that the cause of this relationship is dust. Using 675 photometrically classified SNe Ia from the Dark Energy Survey 5-yr sample, we study the differences in Hubble residual for a variety of global host galaxy and local environmental properties for SN Ia subsamples split by their colour. We find a 3σ difference in the mass-step when comparing blue ( c < 0) and red ( c > 0) SNe. We observe the lowest r.m.s. scatter (∼0.14 mag) in the Hubble residual for blue SNe in low mass/blue environments, suggesting that this is the most homogeneous sample for cosmological analyses. By fitting for c -dependent relationships between Hubble residuals and M stellar, approximating existing dust models, we remove the mass-step from the data and find tentative ∼2σ residual steps in rest-frame galaxy U − R colour. This indicates that dust modelling based on M stellar may not fully explain the remaining dispersion in SN Ia luminosity. Instead, accounting for a c -dependent relationship between Hubble residuals and global U − R, results in ≤1σ residual steps in M stellar and local U − R, suggesting that U − R provides different information about the environment of SNe Ia compared to M stellar, and motivating the inclusion of galaxy U − R colour in SN Ia distance bias correction.